Advances in Italian Mechanism Science : proceedings of the First International Conference of IFToMM Italy - Boschetti, Giovanni; Gasparetto, Alessandro (Springer, 2016)
This volume contains the Proceedings of the First International Conference of IFToMM Italy (IFIT2016), held at the University of Padova, Vicenza, Italy, on December 1-2, 2016. The book contains contributions on the latest advances on Mechanism and Machine Science. The fifty-nine papers deal with such topics as biomechanical engineering, history of mechanism and machine science, linkages and mechanical controls, multi-body dynamics, reliability, robotics and mechatronics, transportation machinery, tribology, and vibrations.
International conference proceedings.
Keywords: Mechanical engineering -- Congresses.; elektronické knihy; electronic books